(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the treatment outcomes of closed tibial shaft fractures using locked intramedullary nailing under fluoroscopic guidance at Ha Tinh Provincial General Hospital. Subjects and Methods: A descriptive study was conducted on 80 patients with closed tibial shaft fractures treated with locked intramedullary nailing under fluoroscopic guidance at Ha Tinh Provincial General Hospital. The study variables included epidemiological characteristics, injury characteristics, surgical features, time to bone union, bone union outcomes, functional outcomes according to the Johner–Wruhs criteria, and postoperative complications. Results: Most patients were over 50 years old (47.5%), with males accounting for 56.3%. The main causes of injury were occupational accidents (42.5%) and traffic accidents (33.8%). Fractures most commonly occurred at the middle third of the tibial shaft (42.5%), and most fractures were comminuted with three or more fragments (65.0%). The mean time to bone union was 22 ± 7.3 weeks. The rate of good bone union was 77.5%, and no cases of nonunion were recorded. Excellent and good functional outcomes accounted for 96.3% according to the Johner–Wruhs criteria. Most patients had no postoperative complications (67.5%). Conclusion: Locked intramedullary nailing under fluoroscopic guidance is an effective and safe method for treating closed tibial shaft fractures, providing a high bone union rate, good functional recovery, and a low complication rate.